Prevalence and causes of vision loss in South-east Asia and Oceania in 2015: magnitude, temporal trends and projections. Issue 7 (12th September 2018) - Keeffe, Jill Elizabeth; Casson, Robert J; Pesudovs, Konrad; Taylor, Hugh R; Cicinelli, Maria Vittoria; Das, Aditi; Flaxman, Seth R; Jonas, Jost B; Kempen, John H; Leasher, Janet; Limburg, Hans; Naidoo, Kovin; et al.
Abstract : Background: To assess prevalence and causes of vision impairment in South-east Asia and Oceania regions from 1990 to 2015 and to forecast the figures for 2020. Methods: Based on a systematic review of medical literature, prevalence of blindness (presenting visual acuity (PVA) <3/60 in the better eye), moderate and severe vision impairment (MSVI; PVA <6/18 but ≥3/60), mild vision impairment (PVA <6/12 but ≥6/18) and near vision impairment (>N5 or N8 in the presence of normal vision) were estimated for 1990, 2010, 2015 and 2020. Results: The age-standardised prevalence of blindness for all ages and both genders was higher in the Oceania region but lower for MSVI when comparing the subregions. The prevalence of near vision impairment in people≥50 years was 41% (uncertainty interval (UI) 18.8 to 65.9). Comparison of the data for 2015 with 2020 predicts a small increase in the numbers of people affected by blindness, MSVI and mild VI in both subregions. The numbers predicted for near VI in South-east Asia are from 90.68 million in 2015 to 102.88 million in 2020. The main causes of blindness and MSVI in both subregions in 2015 were cataract, uncorrected refractive error, glaucoma, corneal disease and age-related macular degeneration. There was no trachoma in Oceania from 1990 and decreasing prevalence in South-east Asia with elimination predicted by 2020. Conclusions: In both regions, the main challenges for eye care come from cataract which remains the main cause of blindness with uncorrected refractive error the main cause of MSVI. The trend between 1990 and 2015 is for a lower prevalence of blindness and MSVI in both regions.